ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI DI KECAMATAN KAPONGAN, KABUPATEN SITUBONDO, PROVINSI JAWA TIMUR - Razzi, Khairur; Arka, Sudarsana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This study aims to analyze the effect of capital, labor, and land simultaneously and partially on rice production; and to analyze the variables that have a dominant effect on rice production. The population in this study were all rice farmers in Kapongan District. The sampling method used in this research is simple random sampling. This research was conducted in 10 villages, from each village 10 farmers were taken as samples, so the total sample was 100 respondents. The data analysis technique used in this research is multiple linear regression. The results showed that the variables of capital, labor, and land simultaneously had a significant effect on rice production in Kapongan District, Situbondo Regency, East Java Province. Labor and land variables partially have a positive and significant effect on rice production, while the capital variable partially has no significant effect on rice production in Kapongan District, Situbondo Regency, East Java Province. Based on the Standardized Coefficients Beta value, where the Standardized coefficients beta value of the capital variable is 0.115, labor is 0.418, and land is 0.398. Because the value of the Standardized coefficients beta of the labor variable has a dominant influence on rice production in Kapongan District, Situbondo Regency, East Java Province.